Fungal Disease in Britain and the United States 1850-2000 : Mycoses and Modernity. - Homei, A.; Worboys, M. (London : Palgrave Macmillan UK, 2013)
This book is open access under a CC BY license. The narrative of 20th-century medicine is the conquering of acute infectious diseases and the rise in chronic, degenerative diseases. The history of fungal infections does not fit this picture. This book charts the path of fungal infections from the mid 19th century to the dawn of the 21st century.
Cover -- Series -- Title -- Copyright -- Dedication -- Contents -- List of Figures and Tables -- Acknowledgements -- List of Abbreviations -- Introduction -- 1 Ringworm: A Disease of Schools and Mass Schooling -- 2 Athlete's Foot: A Disease of Fitness and Hygiene -- 3 Candida: A Disease of Antibiotics -- 4 Endemic Mycoses and Allergies: Diseases of Social Change -- 5 Aspergillosis: A Disease of Modern Technology -- Conclusion -- Notes -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books